Modification of Expression of Pluripotency Genes in Ehrlich's Carcinoma Cells Following Cryopreservation - Chelombitko, Olga V.; Bondarovich, Nikolay A.; Ostankov, Maksim V.; Dimitrov, Aleksey Yu.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):182.